Dental volumetric tomographical evaluation of location and prevalence of maxillary sinus septa - Ibrahim Damlar; Burcu Keles Evlice; Sule Nur Kurt (Çukurova Üniversitesi Tıp Fakültesi Dergisi, 2013)
Purpose: The aim of this study was to determine the prevalence and location of maxillary sinus septa with the help of dental volumetric tomography. Methods: 760 patients’ 1520 maxillary sinus were evaluated by dental volumetric tomography for detecting maxillary sinus septa. Maxillary sinus was divided into 3 zones (anterior, middle and posterior zones) while location of the maxillary sinus septa. Results: 47 of maxillary sinus septa existed in the anterior zone (24.7%), 35 of them in the middle zone (18.4%) and 108 of them in the posterior region (56.8%). Conclusion: The formation of the maxillary sinus septa was affected by the existence or lack of the teeth. Correct detection of the presence of maxillary sinus septa was important prior to sinus lifting and dental implant surgery. Dental volumetric tomographical evaluation of maxillary sinus septa was more useful for a correct diagnosis and treatment planning. [Cukurova Med J 2013; 38(3.000): 467-474]